EMR continuance usage intention of healthcare professionals. (3rd April 2017) - Sayyah Gilani, Mina; Iranmanesh, Mohammad; Nikbin, Davoud; Zailani, Suhaiza
ABSTRACT: Electronic medical records (EMRs) have been proven to be effective tools for improving the safety and quality of healthcare despite their relatively low usage rate in hospitals. The long-term development by EMRs depends on the continued use of healthcare professionals. In this study, technology continuance theory (TCT) was used to evaluate the short-term and long-term continuance acceptance of EMRs among healthcare professionals. Data were gathered by surveying 195 medical professionals in Iran. The data were analyzed using the partial least squares (PLS) technique. The analysis showed that the TCT provided a deep understanding of user continuance intention toward EMRs. In addition, the findings illustrated that the determinants of continuance intention vary between short-term and long-term users. The theoretical and practical implications of the study are discussed.